Rancang Bangun Aplikasi Mobile Virtual Tour Menggunakan Foto 360° dengan Objek Penelitian Museum Nasional : Indonesia - Muhammad Ammar Robbani; Yusep Rosmansyah (Jurnal Sistem Cerdas, 2021)
Virtual reality (VR) is a technology that can make people experience something immersive, one of which is for virtual tours. Virtual tours are a new way of doing digital tours so that users can see the location of these tourist attractions even though they are very far away. With the Large-Scale Social Restrictions (PSBB) due to the Covid-19 pandemic, currently, people cannot travel freely as before. Because of this, virtual tours have great potential for people who want to experience visits to tourist attractions without having to visit directly, although they cannot replace the experience of visiting tourist attractions directly, the use of virtual tours can provide new tourist experiences for the community. Therefore, a virtual tour application solution is designed and built to be able to offer the experience of visiting tourist attractions indirectly to the public. The object of research for the virtual tour application is the National Museum. In making this application, it will use a 360 ° photo to be able to represent the location of the tourist spot in real terms. Based on the results of testing the effect of the application, it is known that the use of VR has an influence on the aspects of education, entertainment and immersion, the overall virtual tour experience and affects the user's intention to visit directly.